Conservation of threatened goat breeds in India. (8th December 2014) - Mandal, Ajoy; Karunakaran, M.; Rout, P.K.; Roy, R.
Summary India is a rich repository of goat genetic resources having 23 well-recognized goat breeds. These breeds have evolved through natural selection and selective breeding by rearers for adaptation to specific agro-ecological conditions. As the indigenous goat breeds of India display great variation in adaptability, productivity, feed utilization, disease resistance, etc. so conservation for unique characteristics of indigenous breeds are of great importance. The recognized breeds of Indian goat population are facing a greater threat due to lack of enforcement of proper breeding policy, inadequate number of breeding bucks, indiscriminate crossbreeding and intermixing among breeds with local animals etc. Considering the current population size, declining rate of population, loss of habitat and introduction of other breeds in the area, the threatened goat breeds are Jamunapari, Beetal, Jakhrana and Surti in the northwestern region, Sangamneri, Osmanabadi, Malabari and Attappady Black in the southern region, Ganjam in the eastern region, and Chegu and Changthangi in the temperate Himalayan region. Furthermore, the positions of several breeds are more or less vulnerable in their breeding tracts. Now, efforts have been made to conserve the indigenous goat breeds for their unique characteristics in their home tracts through in-situ and ex-situ conservation in different agroclimatic regions of India.